The Impact of the Holocaust in America The Jewish Role in American Life (Purdue University Press, 2008)
The contributions to this volume consider topics such as the immigrant experience in coming to America after the trauma of the Holocaust; how the Shoah has shaped more recent interpretation of the Hebrew Bible; the role that survivors have fulfilled in educating American youth not only about the Holocaust itself, but also about how values - especially in regard to tolerance - can and must be shaped by eye-witness testimony on the Shoah; the impact of Holocaust in film, especially in "third-generation" cinema; the issues and difficulties of presenting the Shoah in children's literature; the dialogue between Christians and Jews, especially in America, and how that dialogue has been constructively influenced and shaped by the Holocaust; the way in which Jewish business activities have altered in the post-World War II environment and in the aftermath of the Holocaust and how the lessons of the Shoah have facilitated the change from nationalist to global economy; how the image and awareness of the Holocaust developed in the American media. For all the range that these articles encompass, throughout them all runs a common theme: that the Holocaust has indelibly marked almost every aspect of American culture. We cannot think of America, American ideals and values, America's role in the world today and the future of America in an increasingly dangerous world, without recognizing that the Shoah casts a long shadow across all these concerns and serves as one of the primary points of horrific historical reference by which we, as Americans, must measure ourselves.